Early vedolizumab trough levels predict treatment persistence over the first year in inflammatory bowel disease. Issue 9 (1st November 2019) - Guidi, Luisa; Pugliese, Daniela; Tonucci, Tommaso Panici; Bertani, Lorenzo; Costa, Francesco; Privitera, Giuseppe; Tolusso, Barbara; Di Mario, Clara; Albano, Eleonora; Tapete, Gherardo; Gremese, Elisa; Papa, Alfredo; et al.
Abstract : Background: Data from trials of vedolizumab for inflammatory bowel disease and from real‐world studies suggest an exposure‐response relationship, such that vedolizumab trough levels may predict clinical and endoscopic outcomes. Objective: The purpose of this study was to evaluate in a prospective observational study the utility of an early vedolizumab trough level assay for predicting the first‐year vedolizumab therapy outcome. Methods: This prospective observational study included consecutive inflammatory bowel disease patients. We measured vedolizumab trough levels and anti‐vedolizumab antibodies at weeks 6 and 14. Clinical outcome was assessed at weeks 6, 14, 22 and 54. The primary endpoint was the correlation between early vedolizumab trough levels and vedolizumab persistence over the first year of treatment, defined as the maintenance of vedolizumab therapy due to sustained clinical benefit. Results: We included 101 patients initiating vedolizumab. A cut‐off vedolizumab trough level of 16.55 µg/ml at week 14 predicted vedolizumab persistence within the first year of therapy, with 73.3% sensitivity and 59.4% specificity ( p = 0.0009). Week 14 vedolizumab trough level was significantly higher in patients with clinical remission at weeks 14, 22 and 54; and in patients achieving mucosal healing within 54 weeks. Conclusion: High vedolizumab trough level at week 14 was associated with a higher probability of maintaining vedolizumab therapy over the first year due to sustained clinical benefit.